Urine mutagenicity and lymphocyte DNA damage in fruit growers occupationally exposed to the fungicide captan. Issue 12 (21st November 2003) - Lebailly, P; Devaux, A; Pottier, D; De Meo, M; Andre, V; Baldi, I; Severin, F; Bernaud, J; Durand, B; Henry-Amar, M; Gauduchon, P
Abstract : Aims: To determine haematological parameters, urine mutagenicity (on three Salmonella typhimurium strains), and DNA damage (using the comet assay) in mononuclear leucocytes of farmers before and after a one-day spraying period of pear and apple trees with the fungicide captan in usual conditions. Methods: Fruit growers were exposed to captan during the 1998 (n = 12) and/or the 2000 spraying seasons (n = 17). Biological samples were collected on the morning of the day of spraying (S1), the evening after spraying (S2), and the morning of the day after (S3). The UK Predictive Operator Exposure Model (UK-POEM) was used to quantify pesticide exposure intensity. Results: No effect was observed on haematological parameters for these two spraying seasons. Proportions of mutagenic urine samples did not significantly differ between S1 and S2/S3 sampling points. In contrast with strains TA97a and YG1041 mainly sensitive to frameshift mutations, a positive trend was observed between the difference (S3–S1) of mutagenic power on strain TA102 detecting base-pair mutations and the exposure predicted value given by UK-POEM, mainly due to parameters related to protective clothing. No significant variations in DNA damage levels were observed between S1 and S3, nor were correlations observed with parameters of pesticide exposure. Conclusions: A one-day spraying period with captan and other pesticides does not significantly induce DNA damages in mononuclear leucocytes. In contrast, an inefficient protective clothing could correlate with an increase in urine mutagenicity as assessed by the TA102 tester strain.